Exosomes Support the Viability of Mesenchymal Stem Cells in the Storage Condition of 4 oC - Thi Trang Uyen, Than; Hoang, Dao Huy (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 3DO - 10.25073/2588-1140/vnunst.5813, 2025)
Umbilical cord-derived mesenchymal stem cells (UCMSCs) and their exosomes have attracted significant attention due to their various potential for therapeutic applications. In this study, we expanded UCMSCs and evaluated several short-term preservation buffers on the cell viability. The results showed that UCMSCs were split up to the 5 th passage (P5), which expressed typical characteristics of mesenchymal stem cells in terms of morphology, marker expression, colony forming, and multilineage differentiation ability. UCMSCs survived up to 48 hours in three preservation buffers. Additionally, three buffers without exosomes were able to maintain a cell survival rate of > 75% at 24 hours for all experiment groups. For the buffers supplied with exosomes, we observed a cell survival rate of > 80% at 24 hours in all experiment groups, and at 48 hours, the percentage of viable cells was higher than that of the buffer group without exosome supplement, except for the group of 2 x 10 6 cells/mL in buffer A (Glucose, Human serum albumin, Heparin calcium, Axit ascorbic, Non-essential amino acid) and C (Ringer lactate), and 5 x 10 6 cells/mL in buffer C. Furthermore, exosomes increased the cell clustering in all three buffer solutions. These results indicate the potential of directly using preservation buffers and cells in vivo and the real application.